Indonesia’s Press Freedom And Law at Twenty-Five: Achievements, Legal Changes And Continuing Challenges - Wiratraman, Herlambang Perdana (Magister of Law, Faculty of Law, University of Mataram, 2025)
Political transition in Indonesia after Soeharto’s regime has been deeply influenced by a decentralised model of governance, which affected to more serious attacks to the journalism. Despite the 1999 Press Law prohibits censorship, banning, and licence, including the dissolving of Department of Information, press freedom has been always disturbed. The extra-judicial killing, physical violence, criminalising against journalism, and other attacks through formal judicial process or other forms, included impunity system, have shown uneasy situation for journalist at field or members of the press to perform journalistic works. The political-economy contestation at the local level plays more important role, rather than the influence of situation and policies at national level. The challenge is the law enforcement to protect journalist at works has been easily deniable and disregarded due to the law system itself that does not give significance effect. The court has been used to collapse media, silencing opposition, retaliating, and terrorising journalism. While the current politics, digital technology shapes press freedom into new challenges, which are more complicated situation due to massive deception and its cyber troops. Hence, this article overviews how press freedom situation and its laws have been shaped at twenty-five years, and what would be possible situation in recent Prabowo’s militarized governance in journalism. By using contextual analysis and historical approach, this article argues on how press freedom in Indonesia has been guaranteed by the law at last twenty-five years, and how Prabowo’s militarized governance shapes press freedom.